A High-Content RNAi Screen Identifies Ubiquitin Modifiers That Regulate TNF-Dependent Nuclear Accumulation of NF-κB - Fraser, Brittany; Maranchuk, Robert A.; Foley, Edan (Frontiers in Immunology, 2014)
The mammalian Tumor Necrosis Factor (TNF) cytokine is a central mediator of inflammato-ry events. Recent studies revealed a number of complex and sophisticated interactions between the TNF pathway and the enzymatic activities encoded by ubiquitin ligases and deubiquitylation enzymes. However, very little is known about the identity of the ubiquitin pathway members that control the extent of ubiquitylation in TNF responses. To address this deficit, we conducted an unbiased, high-content screen of the human ubiquitin pathway for gene products that control de-fining features of the cellular response to TNF. In particular, we sought to identify ubiquitin modifying enzymes that alter the ability of TNF to regulate the nuclear accumulation of NF-κB. In this screen, we identified and validated several novel regulators of the TNF pathway. We be-lieve these regulators constitute potential targets for pharmacological interventions that manipu-late TNF-dependent inflammation.